1998
DOI: 10.1021/jm970590k
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity of Novel Rhodacyanine Dyes as Antitumor Agents

Abstract: We have previously reported that rhodacyanine dyes, such as 1 and 2, exhibited a potent inhibitory effect on the growth of several tumor cells and that 4-oxothiazolidine (rhodanine) was an essential moiety for antitumor activity. On the basis of our foregoing work, two types of rhodacyanine dyes, which categorized into class I and II depending on the methine length, were synthesized and evaluated as a novel antitumor agent. Attention was particularly focused on the structure-activity study of two heteroaromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 7 publications
2
63
0
1
Order By: Relevance
“…Therefore, we tentatively concluded that the electronic influences of the substituent in the phenyl ring appear to play an important role in activity, and this behavior depends on the cancer cell lines to which they are In the present study, the coupling between indolin-2-one and 5-benzylidene-4-thiazolidinone systems led to several compounds with better anticancer activity than the previously reported analogues [15,23,24]. Two neutral conjugate systems integrated at the 4-thiazolidinone moiety may contribute to the anticancer activity of these compounds, which has already been partially confirmed by anticancer activity of the rhodacyanine dyes [25].…”
Section: Biological Results and Discussionsupporting
confidence: 75%
“…Therefore, we tentatively concluded that the electronic influences of the substituent in the phenyl ring appear to play an important role in activity, and this behavior depends on the cancer cell lines to which they are In the present study, the coupling between indolin-2-one and 5-benzylidene-4-thiazolidinone systems led to several compounds with better anticancer activity than the previously reported analogues [15,23,24]. Two neutral conjugate systems integrated at the 4-thiazolidinone moiety may contribute to the anticancer activity of these compounds, which has already been partially confirmed by anticancer activity of the rhodacyanine dyes [25].…”
Section: Biological Results and Discussionsupporting
confidence: 75%
“…In the last decades, interests in cyanine dyes [1] are rapidly increasing due to their wide application areas such as sensitizers in photographic industry [2], laser dyes [3,4], anti-tumor agent [5], non-linear optics [6], optical disk as recording media [7] and fluorescence probe for biological molecules [8].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of 7 are comparable with quinine (1) and chloroquine (2) treatment (entries 4, 5). MKT-077 (7a) [17][18][19] was developed as a potential antitumor agent by FUJIFILM Co. based on the DLC hypothesis, originally proposed by Chen. 20) He proposed that π-delocalized lipophilic cations (DLCs) could penetrate the hydrophobic barriers of the plasma and mitochondria membrane under a cross-membrane negative potential.…”
Section: π-Delocalized Lipophilic Cationic Motifmentioning
confidence: 99%